Development and performance evaluation of plantain peeler cum slicer - ASWATHI K.B INDULEKSHMI; Er. Rajesh G.K (Guide) (Tavanur 2010 Department of Post-Harvest Technology and Agricultural Processing)
Development and performance evaluation of plantain peeler cum slicer
Development and performance evaluation of plantain peeler cum slicer